ANALISIS PENGARUH FILLER ABU SERABUT KELAPA TERHADAP STABILITAS DAN KEPADATAN PADA ASPAL AC-WC NR - Bagus Fajri; Farlin Rosyad (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
This study aims to analyze the effect of using coconut fiber ash as a filler on the stability and density of AC-WC type asphalt mixtures using SIR 20 rubber asphalt. The abundant and underutilized coconut fiber waste encourages this research as an innovation for alternative filler materials in road pavement mixtures. The method used is a laboratory experiment with variations in coconut fiber ash content of 0%, 4%, 6%, 8%, and 10% of the total filler. Each variation was tested using the Marshall method to assess stability, flow, VIM, VMA, VFA, and Marshall Quotient (MQ). The results show that the addition of coconut fiber ash influences the improvement of the mixture's stability and density. The optimum variation was obtained at a certain filler content that provided the best balance between high stability, appropriate flow, and VIM and VFA values within the Bina Marga specifications. Therefore, coconut fiber ash has the potential to be used as an environmentally friendly and economical alternative filler in road pavement construction. Keywords: Coconut fiber ash, AC-WC, filler, stability, density, Marshall.